Use of atypical forms of employment in breach of the law – introduction to the discussion (The use of atypical forms of employment in violation of labour and social security laws - diagnosis and prospects for the future, 2023)
The aim of the chapter is to introduce the reader to the issue of the use of atypical forms of employment in violation of labour law and social security law, which was the subject of the 5th jubilee All- Polish Scientific Conference of the series “Atypical Employment Relations”, organised in Łódź on 1–2 December 2022 in a hybrid formula, both at the Faculty of Law and Administration of the University of Łódź and via the Internet. The event was organised by the Centre for Atypical Employment Relations and the Student Scientific Forum on Atypical Employment Relations of the Faculty of Law and Administration of the University of Łódź, as well as the Regional Labour Inspectorate in Łódź. The author presents his own reflections on the issues covered by the conference.